Influence of inquiry learning model and motivation on pancasila education learning outcomes - Ambadatu, Agustinus; Rahman, Ujang; Atiqoh, Atiqoh (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
This study examined the effects of the guided inquiry learning model and learning motivation on Pancasila Education outcomes among 11th-grade students at SMA Bhakti Mandala Nabire (n = 47). Using a quasi-experimental method with a 2×2 factorial design, the research employed validated and reliable instruments to collect data on learning outcomes and motivation. The two-way ANOVA results revealed significant main effects of both the learning model and motivation, while their interaction was not statistically significant. Descriptively, students with high motivation taught using the guided inquiry model achieved the best results. These findings suggest that teachers should adopt the guided inquiry approach to enhance student engagement and improve academic performance in Pancasila Education